Axillary ultrasound-guided approach for the brachial plexus in pig cadavers: A descriptive study. (April 2022) - Trujanovic, Robert; Verdier, Natali; Calice, Ivana; Knecht, Christian; Otero, Pablo E
Effective multimodal analgesia techniques are required when pigs are used as models in orthopedic human research. Regional anesthesia is a widely used technique to provide perioperative analgesia in animals undergoing orthopedic surgery. The brachial plexus (BP) block is indicated to desensitize the forelimb in many species but has not been yet described in pigs. The main aims of this study were to develop an ultrasound-guided axillary approach for the BP and to evaluate injectate spread and nerve staining in pig cadavers. Eight fresh F1 cross breed German Large White and German Landrace male pig cadavers were enrolled. Two cadavers were used for anatomical dissection of the axillary space and to determine the disposition of the BP. Six cadavers were used to perform a bilateral axillary ultrasound-guided approach for the BP, and after injecting 0.3 ml/kg of a solution of 2% lidocaine and new methylene blue (L-NMB), these were dissected to determine injectate spread and nerve staining. Upon dissection, the BP was observed in all the cases surrounded by the axillary sheath and in close proximity to the axillary artery. Ultrasonographic scanning and guidance for the approach to the BP was feasible in all cadavers and upon dissection, all the nerves forming the BP were stained in all their quadrants and in all the cases. In conclusion, the injection of 0.3 ml/kg of L-NMB through an ultrasound-guided axillary approach to the BP was feasible and adequate to entirely stain the BP in all pig cadavers. Further clinical studies are required to evaluate the effectiveness of this technique in live animals.